State Bar Pro Bono Conference in Los Angeles - Watkins, Howard::::::::: (1985)
Audience listening to keynote speaker; center table: ?, Henry Der, Toby Rothschild, Tanya Naiman, Dan Bradley, Leroy Cordova, Patricia Lee and ?